(untitled) (Research, Society and Development, 2022)
Burning Mouth syndrome (BAS) is a disorder characterized by a burning sensation, associated with dryness, loss or alteration in taste and psychosocial distress, in which the oral mucosa is clinically normal and no causal factor is found. The burning sensation is bilateral and the tongue is the most commonly affected site. There seems to be a higher prevalence in females, especially over the age of 50. The etiology is multifactorial, and one of the factors associated with the development of SAB is the change in hormonal parameters typical of the menopausal period. However, the clear scientific understanding of this interrelationship still remains unclear. The objective of this integrative review was to evaluate current studies that report an association between Mouth Blistering Syndrome and hormonal changes. Through the analysis of related articles in the PubMed, Web of Science, and Embase databases from 2016 to 2021. The descriptors "burning mouth syndrome" and "hormone" were used together and no language restrictions were imposed. A total of 61 articles were found, but 14 papers were included in this research. According to the literature searched, the influence of hormonal changes on SAB seems plausible. The selected articles provided evidence of this interrelationship. However, further studies are still needed to assure this interrelationship, as well as the mechanism by which it occurs.